Aktualisasi Nilai Pancasila dalam Upaya Membangun Karakter Anak di Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Nurul Ilmi Kabupaten Bandung - Asnia Putri Diningrum; Alif Mukti Arrasyidin; Azzahra Lailatul Badriyah; Safna Sa’diyah; Rafie Muhammad Syabani; Reffa Cempaka Indah; Gilang Adi Pratama; Abdul Halim Al Ghifari; Fikri Firdaos; Rani Khaerunnisa; Dian Herdiana (Yayasan Daarul Huda Kruengmane, 2025)
Pancasila, as the foundation of the state and a guideline for the life of society, needs to be applied concretely in daily activities so that it does not remain merely an idea without practice. Instilling the values of Pancasila is important from early childhood, as children at this stage are more easily guided and shaped. This activity focuses on internalizing the values of the first principle, “Belief in the One and Only God,” and the third principle, “The Unity of Indonesia,” through the introduction of religious teachings according to each child's belief and the habituation of attitudes such as mutual respect and cooperation. Group 1 of the Pancasila Education course at the State Islamic University Sunan Gunung Djati Bandung carried out an activity to actualize Pancasila values at Madrasah Diniyah Takmiliyah Awaliyah Nurul Ilmi, Kp. Tanjakan Muncang RT 002/RW 007, Cileunyi Wetan Village, Cileunyi District, Bandung Regency, on October 28, 2025. The material provided included introductions to basic Islamic teachings and daily prayers, delivered through learning-by-playing methods and the provision of gifts as motivation for the children. This activity aims to help the students understand religious values and the value of unity in a simple way, enabling them to practice these values in their daily lives.